Evaluation of Effectiveness of Ethanolic Extract of Artemisia aucheri, Individually and in Combination with Chloroquine, on Chloroquine - Sensitive Strain of Plasmodium berghei in Sourian Mice. - Masomeh Khodadadi; Mehdi Nateghpour; Effat Souri; Leila Farivar; Afsaneh Motevalli Haghi; Abbas Rahimi-Froushani; Zeinab Karbalaei (Tehran University of Medical Sciences, 2013)
Drug resistance in malaria parasites is extending in the world particularly in chemical synthesized drugs such as 4- aminoquinolines and aminoalcoholes. Employing herbal extracts is encouraged by WHO in the malarious areas. In this study, the effectiveness of ethanolic extract of Artemisia aucheri individually and in combination with chloroquine, has been considered against chloroquine - sensitive strain of Plasmodium berghei.At the first stage, ED50 of A. aucheri and chloroquine on P. berghei was calculated using in vivo test. Then based on the ED50s combination of A. aucheri and chloroquine with ratios of 0/100,10/90,20/80,30/70,40/60,50/50,60/40,70/30,80/20,90/10 and100/0 were tested against the parasite. For evaluating the adverse effect of A. aucheri on the mice, for two weeks 1000mg/kg of the extract was daily employed and the mice were followed up for fifty days.ED50s for chloroquine and A. aucheri were 1.6mg/kg and 1000mg/kg respectively. The outcome of two drugs combination on the mice showed antagonistic effects on the chloroquine - sensitive strain of parasite. Two weeks daily administration of A. aucheri had no toxic effect on the mice.A. aucheri individually can be effective in reducing the parasite while in combination with chloroquine loses its property.